Efficient implementation of adaptive interpolation filters for low complexity video coding - Ugur, K.; Rusanovksyy, D.; Hallapuro, A.; Lainema, J.; Gabbouj, M. (IEEE transactions on consumer electronics, 2009)
This paper presents novel methods for implementing adaptive interpolation filtering techniques for video coding on 16-bit integer architectures. The proposed methods offer significant complexity reduction over the state-of-the-art, making them especially valuable for resource constrained mobile multimedia devices, with high coding efficiency.